2020
DOI: 10.32598/ppj.24.3.60
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of novel selena-diazole derivative against oxidative stress induced by dipyrone in female rats

Abstract: Introduction: Selena-diazole has antioxidant, and antitumor activities. Also selena-diazol exhibited promising antifungal, antibacterial, viral infection and neurodegenerative disease. The aim of the study is to evaluate the antioxidant activity of a novel -(4,5,6,7-tetrahydro- [1,2,3-] selenadiazolo [4,5 e] pyridine-4,6-diyl) bis(benzene-1,3-diol) (T) against dipyrone (Di) induced oxidative stress. Methods: In vitro antioxidant using DPPH, concentrations of T and ascorbic acid (AA) at 10, 20, 30, 40 and 50μg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Similar to our study, studies of Nadheerah et al 2019 and Sabah Ansar et al 2017 discovered minor differences in liver physiology between control and Se treated groups. Histopathological investigation revealed that selenium has a protective effect against AAP-induced liver damage (41)(42) .…”
Section: Histopathological Examination Effect On Livermentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to our study, studies of Nadheerah et al 2019 and Sabah Ansar et al 2017 discovered minor differences in liver physiology between control and Se treated groups. Histopathological investigation revealed that selenium has a protective effect against AAP-induced liver damage (41)(42) .…”
Section: Histopathological Examination Effect On Livermentioning
confidence: 99%
“…Second, selenium influences phagocytes, immunoglobulin, and T cells to enhance human immunity. Third, selenium is crucial for thyroid function, which affects renal hemodynamics (44) . In a study with 1,871 participants, Hiragi et al (2018) provided epidemiological data on the relationship between AAP overdose and the frequency of acute renal damage.…”
Section: Effects On Kidneymentioning
confidence: 99%